(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2022)
This paper analyses the posthumous editions of Vincenzo Monti’s Mascheroniana canto IV and V. The two texts were not published during author’s lifetime, and they circulated among Monti’s closest friends only. Consequently, it has been necessary clarifying the source of the text printed by the very first publishers and investigating the work of the editors, which turned out to be arbitrary as it doesn’t mirror the intentions of Monti.